Konten Informatif Dan Edukatif Terhadap Kesadaran Merek Restoran ShukaGrill - Tiyas Tirani; Mariana Rista Ananda Siregar; Sabila Adinda P. Andarini (Journal of Media and Communication | E-ISSN : 3063-9581, 2024)
The purpose of this study is to find out about the relationship between Social Media Marketing Instagram account @shukagrill Brand Awareness (Case Study of All You Can Eat Restaurant with Three Furnaces). The independent variable (X) is social media marketing and the dependent variable (Y) is brand awareness. The indicators used for Social Media Marketing variables are Content Creation, Content Sharing, Connecting, and Community Building. Brand Awareness indicators include Unaware of Brand, Brand Recognition, Brand Recall, and Top of Mind. This research uses a descriptive approach with Quantitative methods. The sample technique uses non-probality sampling with the criteria of followers of @shukagrill Instagram account. This study was conducted by distributing questionnaires and observations to 164 respondents. It was found that there was a relationship between social media marketing and brand awareness through Instagram @shukagrill of 3,58 in the high category. Respondents get information about AYCE three furnace products through content produced by Instagram accounts @shukagrill which are informative, clear, and educational. These results can clearly be seen that there is a unidirectional or positive relationship.